If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 2) * ln(2) = ln(360) Reorder the terms: (2 + x) * ln(2) = ln(360) Reorder the terms for easier multiplication: 2ln(2 + x) = ln(360) (2 * 2ln + x * 2ln) = ln(360) (4ln + 2lnx) = ln(360) Reorder the terms for easier multiplication: 4ln + 2lnx = 360ln Solving 4ln + 2lnx = 360ln Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-360ln' to each side of the equation. 4ln + -360ln + 2lnx = 360ln + -360ln Combine like terms: 4ln + -360ln = -356ln -356ln + 2lnx = 360ln + -360ln Combine like terms: 360ln + -360ln = 0 -356ln + 2lnx = 0 Factor out the Greatest Common Factor (GCF), '2ln'. 2ln(-178 + x) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-178 + x)' equal to zero and attempt to solve: Simplifying -178 + x = 0 Solving -178 + x = 0 Move all terms containing l to the left, all other terms to the right. Add '178' to each side of the equation. -178 + 178 + x = 0 + 178 Combine like terms: -178 + 178 = 0 0 + x = 0 + 178 x = 0 + 178 Combine like terms: 0 + 178 = 178 x = 178 Add '-1x' to each side of the equation. x + -1x = 178 + -1x Combine like terms: x + -1x = 0 0 = 178 + -1x Simplifying 0 = 178 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 4x+164=12x-12 | | 4x+64=12x-12 | | 114-3x=15x+16 | | 114-3x= | | x=x-2*(2x-4) | | (X-3)(X+6)-10=0 | | 7-7x=159-35x | | X(X-4)-21=0 | | 4y^2-2=12y | | 3(x-3)=3 | | n=4000 | | 7XY^2-5XY(2-Y)=0 | | -9X^2+8X=0 | | 5t+10-6= | | -X^2+11X=0 | | -5X^2-28X+12=0 | | -5X^2-28X=12 | | x^2-x-18=0 | | 3*-12-6*-12+12=-4*-12 | | x=(95000+x)*0.04 | | x=(95000+x)*0.004 | | y=7.87-0.025(40) | | 3s+-4(8+-53)=14 | | y=7.87-0.025(10) | | y=7.18-0.027(10) | | y=7.18-0.027x | | y=7.18-0.027(40) | | 6(3.2y+1)=3.6 | | y=7.23-0.033(40) | | y=7.23-0.033(10) | | 3x-6x+12=-4x | | 3y+5=8+2y |